Integrative assessment of the effects of ventilation systems on economic efficiency, milk production, and reproductive performance in dairy cows - Peker, Arzu; Magrin, Luisa; Segato, Severino; Mondin, Chiara; Orkan, Şükrü; Öztürk, Nurşen; Gottardo, Flaviana; Trestini, Samuele (Frontiers in Veterinary Science, 2025)
Due to global warming, temperate regions are increasingly experiencing heat waves, which negatively impact dairy cow welfare, productivity, and farm profitability. Ventilation systems (VSs) are a common heat mitigation strategy, despite their high initial investment cost. This study investigated the effects of heat stress (HS) and VSs on dairy cows’ milk yield and whether VSs guarantee an economic benefit for farmers. The trial involved four dairy farms over 3 years: 2 years before and one after VS installation. We conducted an observational within-farm pre-post study, using two pre-installation years and 0.5–1 post-installation year per farm. The following outcomes were analyzed at the herd level: daily milk yield, biweekly milk quality, and monthly reproductive metrics. The temperature-humidity index (THI) was calculated daily as a measure of HS and categorized as follows: comfort (<72), mild discomfort (72–79), discomfort (80–84), and alert (>84). Economic sustainability was assessed through partial budget analysis, accounting for additional feed, labor, and electricity costs. The presence of VSs was associated with a significant increase in cows’ milk yield across all THI conditions (p < 0.001). Fat and protein contents decreased following VS installation, consistent with the observed increase in milk yield. However, their values were significantly lower under the most critical THI classes (p < 0.001). Linear somatic cell count (SCC) scores were higher under the discomfort and alert THI classes in the absence of VSs, whereas they decreased slightly across THI classes when VSs were used (p < 0.001). The duration of lactation, days open, and number of services per pregnancy reached their highest values under THI alert conditions in the absence of VSs and were significantly reduced following the implementation of VS (p < 0.001). Increased milk income with VS use was €12.39/day/cow under mild discomfort, €12.23 under discomfort, and €12.08 under alert conditions. The results showed wide variability in economic outcomes across farms and THI classes. Although differences in VS management prevented a definitive conclusion regarding return on investment (ROI), the findings suggest positive effects on cows’ productivity and farm profitability. However, a definitive ROI could not be stated due to heterogeneity in fan size/spacing, cows-per-fan coverage, and farm-specific post-installation durations. Therefore, future cost–benefit analyses should consider additional factors to fully evaluate VS investments.